Lettres intimes - Berlioz, Hector 1803-1869; Gounod, Charles 1818-1893 (Paris Calmann-Lévy, 1882)
Lettres 10 juin 1825 - 22 octobre 1867
avec une préface par Charles Gounod
Keywords: 19th Century (1801-1900); Composer; Correspondence; Biography; France